Preorthodontic corticotomy and simultaneous bone augmentation in the prevention of buccal alveolar dehiscences - Pál Nagy; Virág Pörzse (Hungarian Dental Association, 2020)
Buccal orthodontic tooth movement (OTM) of the anterior teeth out of the osseous envelope of the alveolar process in case of front teeth crowding may be associated with a higher tendency for developing gingival recessions. The aim of this case report is to present the effectiveness of a minimally invasive preorthodontic corticotomy combined with a buccal bone augmentation according to the rules of periodontally accelerated osteogenic orthodontics (PAOO). The main goal of our therapy is to increase or maintain the buccal bone thickness, which could prevent the development of gingival recessions. Corticotomy possibly have an additional benefit throughout regional acceleratory phenomenon, reducing the duration of OTM in the early treatment phases. A generally and periodontally healthy individual at the age of 17 presenting crowding and thin bone morphotype in the mandibular y front area, who requiresting OTM with incisor proclination, was treated. Surgery was performed under local anesthesia. Three vertical incisions were performed on the midline and on both sides between lateral incisors and canines, with preservation of the papilla integrity. Incisions were connected by tunneling knifes in 2 layers, subperiosteally in the whole length and supraperiosteally apically from the mucogingival junction. Corticocisions were utilized by ultrasonic instrument penetrating through the cortical bone. "Sticky bone" plates, a combinations of platelet rich fibrin (PRF) and xenograft, were used subperiosteally for bone, and PRF membranes supraperiosteally for soft tissue augmentation. Initiation of OTM started 1 week postoperatively, and activation of the multibond appliance was performed activated in 2 weeks. The extent of tooth movement measured on the central incisor was compared followed-up on cephalometric radiographs made taken at the different treatment time appointments, while buccal bone thickness on the 6 front teeth was evaluated in CBCT before and after OTM. The alignment phase ended up at the 20th week due to an initial arch wire sequence using light forces. The buccal bony wall thicknesses showed similar values compared to the initial ones, and there was no radiologically proven substantial vertical bone loss. The presented comprehensive treatment approach promised a good option in the prevention of the periodontal side effects during orthodontic treatment.